Effect of feeds with different crude fiber content on the performance of meat goose - Dobos, Ádám; Bársony, Péter; Posta, János; Babinszky, László (Acta Agraria Debreceniensis, 2019)
In the last 50 years, poultry meat production has increased dynamically. The role of crude fiber content in feed is unclear based on a small amount of literature about goose feeding.The aim of theis experiment was to determine how various crude fiber content (55; 60; 65g crude fiber/kg feed) influences the performance of meat geese in the second phase of the rearing period. 150 goslings (3 treatments, 5 cages/treatment, 10 birds/cage) were included in the test. The experiment started and finished at the age of 21st and 63rd  day, respectively.The obtained results suggest that various crude fiber content did not influence the performance of meat geese significantly; however, a feed of 55g crude fiber/kg resulted in better fattening results (final body weight, body weight gain, specific feed protein and energy conversion rate). In addition, compound feed of 65g crude fiber/kg proved more favourable with respect to cost-efficiency. Based on the obtained results so far, further models and farm experiments are required.